2017
DOI: 10.1021/acschembio.7b00776
|View full text |Cite
|
Sign up to set email alerts
|

Backbone Circularization Coupled with Optimization of Connecting Segment in Effectively Improving the Stability of Granulocyte-Colony Stimulating Factor

Abstract: Backbone circularization of protein is a powerful method to improve its structural stability. In this paper, we presumed that a tight connection leads to much higher stability. Therefore, we designed circularized variants of a granulocyte-colony stimulating factor (G-CSF) with a structurally optimized terminal connection. To estimate the appropriate length of the connection, we surveyed the Protein Data Bank to find local structures as a model for the connecting segment. We set the library of local structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 48 publications
(78 reference statements)
2
36
0
Order By: Relevance
“…). This was consistent with the order of the apparent T m values determined by evaluating the loss of secondary structure with increasing temperatures . The apparent T m includes information about reversible unfolding and subsequent irreversible denaturation (i.e., aggregation).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…). This was consistent with the order of the apparent T m values determined by evaluating the loss of secondary structure with increasing temperatures . The apparent T m includes information about reversible unfolding and subsequent irreversible denaturation (i.e., aggregation).…”
Section: Discussionsupporting
confidence: 84%
“…Cysteine bridge reduction by the addition of dithiothreitol led to a 4‐Da increase in the molecular mass of all variants, indicating that two disulfide bonds were formed in each variant. In the previous study , we had shown that the native G‐CSF and G‐CSF variants (used in the current study) had similar binding affinities to the G‐CSF receptor. This suggested that these variants retained the original conformation of the native G‐CSF including the native connectivity of the two disulfide bonds.…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations